2007
DOI: 10.1029/2006jd007369
|View full text |Cite
|
Sign up to set email alerts
|

Methane carbon isotope effects caused by atomic chlorine in the marine boundary layer: Global model results compared with Southern Hemisphere measurements

Abstract: [1] Recent measurements of the apparent kinetic isotope effect (KIE) of the methane (CH 4 ) atmospheric sink in the extratropical Southern Hemisphere (ETSH) have shown the apparent KIE to be larger in magnitude than expected if the sink were the hydroxyl radical (OH . ) alone. We present results from simulations using the U.K. Met Office's Unified Model (UM) to evaluate whether atomic chlorine (Cl . ) in the marine boundary layer (MBL) could give this effect. We modify the UM to include sources of 12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
179
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(190 citation statements)
references
References 29 publications
8
179
3
Order By: Relevance
“…Uncertainties in the removal rates of methane [26][27][28] and a widening range of indirect effects for this gas [7] are also creating growing issues for the use of the GWP in a policy framework.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainties in the removal rates of methane [26][27][28] and a widening range of indirect effects for this gas [7] are also creating growing issues for the use of the GWP in a policy framework.…”
Section: Resultsmentioning
confidence: 99%
“…The methane lifetime has additional uncertainty owing to its removal by stratospheric processes and a soil sink. In addition, there is now strong evidence, based on carbon isotopic measurements, for an additional sink similar in magnitude to that of the stratospheric and soil chemistry processes and linked to atmospheric chlorine [26][27][28]. Whether or not this fourth sink for methane is variable or is undergoing a trend is still unknown, as are its implications for long-term pathways to climate stabilization.…”
Section: Issues With Global Warming Potentialsmentioning
confidence: 99%
“…Allan et al (2005) measured mixing ratios of methane and δ 13 C-CH 4 at two stations in the Southern Hemisphere from 1991 to 2003 and found that the apparent kinetic isotope effect of the atmospheric methane sink was significantly larger than that explained by OH alone. A seasonally varying sink due to atomic chlorine (Cl) in the marine boundary layer of between 13 and 37 Tg CH 4 yr −1 was proposed as the explaining mechanism (Allan et al, 2007). This sink was estimated to occur mainly over coastal and marine regions, where NaCl from evaporated droplets of seawater react with NO 2 to eventually form Cl 2 , which then UV dissociates to Cl.…”
Section: Tropospheric Reaction With CLmentioning
confidence: 99%
“…The main atmospheric sink of methane is its oxidation by the hydroxyl radical (OH), mostly in the troposphere, which contributes about 90 % of the total methane sink (Ehhalt, 1974). Other losses are by photochemistry in the stratosphere (reactions with chlorine atoms, Cl, and atomic oxygen, O( 1 D)), by oxidation in soils (Curry, 2007;Dutaur and Verchot, 2007), and by photochemistry in the marine boundary layer (reaction with Cl; Allan et al, 2007;Thornton et al, 2010). Uncertainties in the total sink of methane as estimated by atmospheric chemistry models are of the order of 20-40 % (Kirschke et al, 2013).…”
Section: Methane Sinks and Lifetimementioning
confidence: 99%
“…The atmospheric lifetime of CH 4 is 9.1 ± 0.9 years (Prather et al, 2012) and most CH 4 is consumed in the troposphere via oxidation by OH radicals, which represents ∼ 90 % of the global CH 4 sink (Prather et al, 2012;Ciais et al, 2013). Soil bacteria known as methanotrophs consume ∼ 9 to 10 % of atmospheric CH 4 and a further ∼ 1 % is oxidized by reaction with chlorine radicals from sea salt in the marine boundary layer (Allan et al, 2007;Ciais et al, 2013).…”
Section: Introductionmentioning
confidence: 99%